Theorising Global Environmental Governance: Key Findings and Future Questions. (January 2015) - Pattberg, Philipp; Widerberg, Oscar
Global environmental governance in the Anthropocene is fundamentally different from older conceptions of environmental policy-making and sustainable development. Environmental problem-solving is no longer concerned with isolated problems, but rather with reorganising the overall relation between humans and natural systems. Empirically, this is reflected in the ever greater attention to questions of institutional interactions (e.g. between the issue areas of economics and environment) and functional overlaps between parallel governance approaches. Normatively, environmental governance in the Anthropocene is concerned with questions of equity and fairness on a finite planet. This article scrutinises the theoretical interregnum in global environmental governance by first sketching the key empirical trends in global environmental governance; secondly, discussing theory-building with regards to four broad areas of inquiry: the questions of agency and authority; the structural dimension of global environmental governance; the related normative questions about legitimacy, accountability, equity and fairness in the Anthropocene; and finally the integration of governance research into formal approaches and the related incorporation of non-social science concepts into environmental governance research. In our conclusions, we propose some initial ideas on how to move forward in the study of global (environmental) governance.